Pengaruh Intensitas Belajar Terhadap Hasil Belajar Siswa pada Mata pelajaran Ekonomi Materi Akuntansi di SMA Negeri 4 Soppeng - Ninin Sarnita Amir; M. Ridwan Tikollah Tikollah; Fajriani Azis Azis (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
This research aims to find out how learning intensity influences the learning outcomes of students who have taken economics accounting subjects at SMA Negeri 4 Soppeng. Learning outcomes are the dependent variable in this research, while learning intensity is the independent variable. The research group consisted of students from SMA Negeri 4 Soppeng class XII IPS 1 and XII IPS 2 who had taken accounting subjects in economics. 50 students were used as a representative sample of the entire population because the sampling method used a total sampling strategy. Documentation and surveys are two techniques used to collect data. For data analysis, instrument testing, hypothesis testing and descriptive percentage analysis were used. With 84.42 percent for learning intensity and 90.24 percent for learning outcomes, the descriptive analyses of learning intensity and learning outcomes are extraordinarily high. The formula Y = 65.656 + 0.453X for learning intensity, which is based on the findings of simple linear regression analysis, shows that the value of learning outcomes increases by 0.453 units for every unit of increase in learning intensity. The hypothesis is accepted since the t-test produced a significant value of 0.000 0.05, demonstrating that learning intensity significantly affects learning outcomes. Meanwhile, (r2) = 0.582%, or 58%, is the result of the examination of the coefficient of determination (r2). This shows that while other factors influence the other 42% of learning outcomes, learning intensity effects or contributes to 58% of them.